Cutaneous lupus tumidus: An unusual unilateral presentation - Samia Mrabat; Hanane aybay; Zakia Douhi; Sara Elloudi; Fatima Zahra Mernissi; Mouna Rimani (Our Dermatology Online, 2021)
Lupus tumidus is a rare subtype of chronic cutaneous lupus erythematosus characterized by erythema and bright urticarial erythematous and violaceous lesions on sun-exposed areas that heal without leaving scars. Lupus tumidus follows a benign and intermittent clinical course and is rarely associated with systemic lupus erythematosus. Treatment involves photoprotection, topical corticosteroids, and antimalarials. We report the case of a 42-year-old patient with an atypical unilateral form of lupus tumidus successfully treated with the administration of hydroxychloroquine in combination with photoprotection and tacrolimus.